1977
DOI: 10.5271/sjweh.2771
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to methylene chloride. Content in subcutaneous adipose tissue.

Abstract: Exposure to methylene chloride. Content in subcutaneous adipose tissue. by Engström J, Bjurström R

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Although skin absorption is recognized as a possible major route of entry for some solvents, it has been studied for only a few. Engstrom and Bjurstrom [1977] found that brief (10-15 minute) immersion of a subject's hands in xylene produced blood concentrations of xylene comparable to those following an 8-hour inhalation exposure at 100 ppm (the threshold limit value [TLV]). The rate of solvent uptake through the skin varies substantially among workers owing to variations in skin thickness, skin perfusion, and the presence of cuts or abrasions of the skin Bird, 19811.…”
Section: Uptakementioning
confidence: 99%
“…Although skin absorption is recognized as a possible major route of entry for some solvents, it has been studied for only a few. Engstrom and Bjurstrom [1977] found that brief (10-15 minute) immersion of a subject's hands in xylene produced blood concentrations of xylene comparable to those following an 8-hour inhalation exposure at 100 ppm (the threshold limit value [TLV]). The rate of solvent uptake through the skin varies substantially among workers owing to variations in skin thickness, skin perfusion, and the presence of cuts or abrasions of the skin Bird, 19811.…”
Section: Uptakementioning
confidence: 99%
“…The elimination of these solvents from adipose tissue in man is relatively slow (1,8,9,10,11,12), a phenomenon indicating a potential risk of prolonged exposure to such lipophilic solvents. In the present study mice were exposed to acetone, as it is of interest to compare the distribution and elimination pattern of the highly water-soluble acetone (19) with those of the earlier studied lipophilic organic solvents.…”
Section: Reprint Requests To: Ms E Wigaeus Researchmentioning
confidence: 99%
“…The concentrations of methylene chloride in subcutaneous adipose tissue after experimental exposure were determined in a previous study from this laboraitory (8,9). Methylene chloride is a vola-tile solvent with a relMi~e'ly :poor affinity for adipose tissue.…”
mentioning
confidence: 99%